2021
DOI: 10.1007/s10566-021-09645-x
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Better: Experiences and Needs of Adolescents and Professionals Regarding Their Mentoring Relationship in Residential Youth Care

Abstract: Background In residential youth care, group care workers and teachers often serve as a mentor for individual adolescents. Although favorable mentoring relationships are associated with positive adolescent outcomes, few studies examined the role of mentoring in residential youth care. Objective The present study aims to assess adolescents’, care workers’ and teachers’ mentoring relationship needs in terms of their one-on-one conversations during residential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the present study, RGC staff were serving in this capacity. Although Harder (2022) found residential care staff were not interested in manualized approaches to mentoring, mentorship training based on best practices and evidence-supported guidelines may help prepare staff and facilitate a recognition of mentoring as a key part of the residential care worker role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, RGC staff were serving in this capacity. Although Harder (2022) found residential care staff were not interested in manualized approaches to mentoring, mentorship training based on best practices and evidence-supported guidelines may help prepare staff and facilitate a recognition of mentoring as a key part of the residential care worker role.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have turned to qualitative methods to further explore youth outcomes in residential care. These inquiries, largely based on European samples (e.g., Harder et al, 2022; Johansson & Andersson, 2006; McCarthy, 2016; Schofield et al, 2017, Slaato et al, 2022) suggest greater nuance than what has often been portrayed in the literature and policy discourse (e.g., Annie E. Casey, 2010; Dozier, 2014). In their systematic review of 12 peer-reviewed, qualitative studies of youth in residential care, Cameron-Mathiassen et al (2022) identified themes in the areas of autonomy and control, relationships and support, safety and security, and transitioning from care.…”
Section: Introductionmentioning
confidence: 99%